Towards measuring the relative biological effectiveness of high-energy neutrons at iThemba LABS - Fairall, Elizabeth (Department of Physics, 2025)
In space, neutrons with energies of up to several TeV are produced through the interac-tions of primary cosmic radiation with matter such as in spacecraft shielding, and in the atmospheres and regoliths of moons and planets. The development of radiation health-risk models for space exploration requires the quantification of the biological effects of neutrons, and in the current radiation protection framework this is achieved via measure-ments of the neutron Relative Biological Effectiveness (RBE). The current deficiency of experimental data regarding the biological effects of high-energy neutrons calls for dedi-cated RBE experiments at neutron energies greater than 20 MeV for the doses, dose rates, and biological endpoints that are relevant to space travel. This project aimed to identify key knowledge gaps and improve neutron radiation risk estimates by developing a stan-dardised approach to measure the limiting maximum value of neutron RBE at low doses (RBEM) at the iThemba Laboratories for Accelerator Based Sciences (LABS) high-energy neutron facility. Data from a preparatory experiment conducted with neutrons produced by a 66.48 MeV proton beam irradiating an 8.0 mm lithium target are used to illustrate the metrological methods for the characterisation of the neutron beam energy distribution and fluence at the iThemba LABS high-energy neutron facility. The metrological characterisation was combined with Monte Carlo radiation transport simulations to establish the absorbed dose delivered to vials containing human peripheral blood mononuclear cells that were irradiated during the experiment. The dosimetry results were related to the correspond-ing observed yield of γ-H2AX foci in the irradiated samples, to obtain dose-response relationships with linear yield coefficients of 10.12 ± 0.63 Gy−1 and 7.45 ± 0.66 Gy−1 for irradiations with neutrons with fluence-weighted average energies of 40.11 ± 0.92 MeV and 37.26 ± 0.40 MeV respectively. The results of this analysis were used to make recom-mendations for future neutron RBE measurements at iThemba LABS at energies relevant to space travel. Such measurements require reliable neutron beam metrology and detailed computational simulations of the experimental setup for both the neutron and reference irradiations, along with appropriate radiobiological analyses.